Testing the adaptive market hypothesis on the WIG Stock Index: 1994-2019 - Kołatka, Marek (Testowanie hipotezy rynków adaptacyjnych dla indeksu giełdowego WIG: 1994-2019, 2020)
The adaptive market hypothesis (AMH) is gaining recognition in the world of science because it coherently and logically reconciles the opinions of representatives of the neoclassical school and of behaviourists. The article assesses the reasons for the application of this hypothesis in the context of the Polish stock market. The aim of the article is to examine the level of predictability of return rates of the main Polish stock exchange index. For this purpose, daily logarithmic return rates were applied from the WIG index from October 1994 to December 2019. Moreover, the occurrence between them of a linear dependence (an autocorrelation test) and non-linear dependence (BDS test) was verified for two-year rolling-window framework. The results obtained confirm the cyclical variability of the level of efficiency for the Polish stock market, which complies with the implications of the adaptive market hypothesis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 131-142
Keywords: adaptive market hypothesis; AMH; market efficiency; return predictability; hipoteza rynku adaptacyjnego; efektywność rynku; przewidywalność stóp zwrotu